Traumatic Reticuloperitonitis in Water Buffalo (Bubalus bubalis): Clinical Findings and the Associated Inflammatory Response. (30th July 2013) - El-Ashker, Maged; Salama, Mohamed; El-Boshy, Mohamed
Abstract : The present study was carried out to describe the clinical picture of traumatic reticuloperitonitis (TRP) in water buffalo ( Bubalus bubalis ) and to evaluate the inflammatory and immunologic responses for this clinical condition. Twenty-two buffalo with acute local TRP were monitored in our study. Additionally, 10 clinically healthy buffalo were randomly selected and served as controls. Acute local TRP was initially diagnosed by clinical examination and confirmed by ultrasonographic (USG) examination and/or necropsy findings. Blood samples were collected from all examined buffalo to measure the respective levels of tumor necrosis factor alpha (TNF- α ), interleukin (IL)-1 β, IL-6, IL-10 and interferon gamma (INF)- γ, serum amyloid A (SAA), C-reactive protein (CRP), haptoglobin (Hp), fibrinogen (Fb), and serum sialic acid (SSA). It was found that TNF- α, IL-1 β, IL-6, IL-10, SAA, CRP, Hp, Fb, and SSA were significantly higher in buffalo with TRP than the controls. Our findings suggest that the examined immunologic variables were helpful in documenting the inflammatory response in buffalo with TRP. However, their diagnostic usefulness only becomes apparent when considered in tandem with the clinical findings for any given animal, its anamnesis, and a subsequent USG assessment. Due to the frequent complications of TRP, more accurate indicators of its occurrence and severity would be useful.